Ozonation of the UV filter benzophenone-4 in aquatic environments: Intermediates and pathways. (April 2016) - Liu, Hui; Sun, Ping; He, Qun; Feng, Mingbao; Liu, Hongxia; Yang, Shaogui; Wang, Liansheng; Wang, Zunyao
Abstract: The occurrence of benzophenone-4 (BP-4) in water environments may pose a serious public health hazard due to its potential endocrine disrupting effects. In this work, the intermediates, probable degradation pathways and toxicity changes during ozonation of BP-4 in aqueous solution were systematically investigated. Results revealed that alkaline conditions favored the oxidation of BP-4. However, inorganic anions (Cl −, NO3 −, SO4 2− ), cations (K +, Ca 2+, Mg 2+ ) and humic acid had no remarkable effect on BP-4 removal within the tested concentrations. Ozonation was also effective for the fast removal of BP-4 in real waters. The TOC suggested a low mineralization rate, even after the complete BP-4 removal. Meanwhile, the treated mixtures exhibited an obvious inhibition to the bioluminescent bacteria Photobacterium phosphoreum, indicating the formation of transformation products with higher toxicities. Furthermore, fourteen products were identified by means of liquid chromatography-mass spectrometry. Notably, seven of them have not been reported previously. The quenching test indicated that the degradation processes probably were dominated by OH. Next, possible degradation pathways were proposed and further justified by theoretical calculations of frontier electron densities. This investigation will contribute to the systematic elucidation of the ozonation process of UV filters in aquatic environments. Highlights: Oxidative degradation of BP-4 was investigated by using the ozonation process. An increased acute bacterial toxicity was found during ozonation. The degradation processes probably were dominated by OH. The main transformation products were identified. Reaction pathways are proposed and justified by FED calculations.